MENINGKATKAN KEMANDIRIAN BELAJAR SISWA BERAGAMA KATOLIK MENCAPAI HASIL BELAJAR FASE F DENGAN MODEL PBL - Julianto Simatupang (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Education creates quality independent humans who are ready to adapt and compete in facing the challenges of global development. Catholic Religious Education and Character Education is one of the subjects that helps students face these challenges with cognitive, affective and psychomotor abilities, demonstrated through increasing learning independence to achieve learning outcomes. This research aims to increase student learning independence so that learning outcomes are achieved. Seeing the situation of students at SMA Negeri 1 Pollung who lack learning independence, this has a big influence on the process of learning activities, where conduciveness is disrupted. The teaching style used by the teacher is also less creative, only centered on the teacher using the lecture method. To overcome the problem of independent learning for students, especially those who are Catholic, the use of the Problem Based Learning (PBL) model or problem-based learning is the appropriate model. The PBL model encourages students to play more of a role in learning activities and the teacher only acts as a facilitator who helps students find their own learning goals. The method used in this research is data collection by observation and assessment. Data is presented in the form of tables, diagrams, descriptions and conclusions drawn from research results. The syntax of the PBL model includes orienting students to problems, organizing students to learn, guiding individual and group investigations with discussion, presenting and developing results, analyzing and evaluating the problem solving process.